KAJIAN MEDICATION ERROR PADA KASUS STROKE DI RS X SURAKARTA TAHUN 2004 - Mutmainah, Nurul (Indonesian Research Gateway)
This work aimed to study the medication error occurred on stroke management at X Hospital in Surakarta during January-October 2004. Subject of the study were in-patient stayed at the hospital during January- July 2004 (retrospective study) and at September-October 2004 (prospective study). Result of the study showed that medication error had been occurred on 49 out 52 patient (94.23%) stayed at the hospital during January-July 2004 and on 16 out 18 (88.89%) patient stayed during September-October 2004. It was revealed that the types of medication error found in retrospective study were prescribing error (26.09%), wrong administration technique (68.12%) and monitoring error (5,9%). Non-rationale antibiotic use was 92.31% and unproper management of hyperglycemic in stroke patient was 45.45%. From prospective study it was revealed that the types of medication error found were prescribing error (25%) and wrong administration technique (75%). Non-rationale antibiotic use was 78.6%, unproper management of hyperglycemic in stroke patient was 12,5%, and medication side effect was 1,92%. ABSTRAK Penelitian ini bertujuan untuk mengkaji kejadian medication error pada terapi stroke di RS X Surakarta selama Januari-Oktober 2004. Subjek penelitian adalah pasien stroke yang menjalani rawat inap di RS X Surakarta periode Januari- Juli 2004 (studi retrospektif) dan periode September-Oktober 2004 (studi prospektif). Dari data yang diperoleh dilakukan kajian penggunaan obat dan outcome pasien yang memberi petunjuk telah terjadinya medication error. Pada studi retrospektif ditemukan adanya kejadian medication error dengan tipe prescribing error (26,09%), wrong administration technique (68,12%) dan monitoring error (5,9%). Penggunaan antibiotik yang kurang tepat ditemukan sebesar 92,31% dan penanganan hiperglikemi pada stroke yang kurang tepat sebesar 45,45%. Dari studi prospektif ditemukan kejadian medication error dengan tipe prescribing error (25%) dan wrong administration technique (75%). Penggunaan antibiotik yang kurang tepat sebesar 78,6%, penanganan hiperglikemi pada stroke yang kurang tepat sebesar 12,5%, dan kejadian efek samping obat sebesar 1,92%. Dari penelitian ini dapat disimpulkan bahwa dari 49 dari 52 (94,23%) pasien stroke pada bulan Januari-Juli 2004 dan 16 dari 18 (88,89%) pasien stroke pada bulan September-Oktober 2004 mengalami kejadian medication error.